The fall of the Amazing Zalindas - Mack, Tracy; Citrin, Michael; Ruth, Greg (New York : Orchard Books, 2006)
The ragamuffin boys known as the Baker Street Irregulars help Sherlock Holmes solve the mysterious deaths of a family of circus tightrope walkers.
Maps on endpapers.
6.3
3-6
Keywords: Holmes, Sherlock (Fictitious character) -- Juvenile fiction; Circus -- Juvenile fiction; Great Britain -- History -- 19th century -- Juvenile fiction; Holmes, Sherlock (Fictitious character) -- Fiction; Circus -- Fiction; Great Britain -- History -- 19th century -- Fiction; Mystery and detective stories; Historical fiction; Holmes, Sherlock (Fictional character) -- Fiction; Circus -- Fiction; Great Britain -- History -- 19th century -- Fiction; Mystery fiction; Historical fiction; Mystery fiction